An algorithm for Path planning with polygon obstacles avoidance based on the virtual circle tangents - Ibrahim, Zahraa Y.; Rashid, Abdulmuttalib T.; Marhoon, Ali F. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
In this paper, a new algorithm called the virtual circle tangents is introduced for mobile robot navigation in an environment with polygonal shape obstacles. The algorithm relies on representing the polygonal shape obstacles by virtual circles, and then all the possible trajectories from source to target is constructed by computing the visible tangents between the robot and the virtual circle obstacles. A new method for searching the shortest path from source to target is suggested. Two states of the simulation are suggested, the first one is the off-line state and the other is the on-line state. The introduced method is compared with two other algorithms to study its performance.